2012
DOI: 10.1186/1741-7015-10-92
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 analogs against antipsychotic-induced weight gain: potential physiological benefits

Abstract: BackgroundAntipsychotic-induced weight gain constitutes a major unresolved clinical problem which may ultimately be associated with reducing life expectancy by 25 years. Overweight is associated with brain deterioration, cognitive decline and poor quality of life, factors which are already compromised in normal weight patients with schizophrenia.Here we outline the current strategies against antipsychotic-induced weight gain, and we describe peripheral and cerebral effects of the gut hormone glucagon-like pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Interestingly, GLP-1 receptor agonists also induce weight loss in both diabetic and nondiabetic patients, 48 and they may therefore be used to treat antipsychotic-induced obesity. [49][50][51] Endogenous GLP-1 levels have been reported in 2 studies 39,41 evaluating the effect of short-term olanzapine treatment in healthy subjects: Vidarsdottir et al 39 showed no effect of olanzapine, whereas Teff et al 41 recently reported increases in postprandial GLP-1 levels. To our knowledge, the present study is the first to report plasma levels of endogenous GLP-1 in patients treated with antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GLP-1 receptor agonists also induce weight loss in both diabetic and nondiabetic patients, 48 and they may therefore be used to treat antipsychotic-induced obesity. [49][50][51] Endogenous GLP-1 levels have been reported in 2 studies 39,41 evaluating the effect of short-term olanzapine treatment in healthy subjects: Vidarsdottir et al 39 showed no effect of olanzapine, whereas Teff et al 41 recently reported increases in postprandial GLP-1 levels. To our knowledge, the present study is the first to report plasma levels of endogenous GLP-1 in patients treated with antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first clinical evidence supporting the use of GLP-1 receptor agonists in the treatment of antipsychotic-induced weight gain (2). To our knowledge, this is the first clinical evidence supporting the use of GLP-1 receptor agonists in the treatment of antipsychotic-induced weight gain (2).…”
Section: Discussionmentioning
confidence: 99%
“…Although oral naltrexone appears to be the most promising among seven therapeutic drugs investigated for gambling (1), poor adherence to oral naltrexone can be a problem (2). Although oral naltrexone appears to be the most promising among seven therapeutic drugs investigated for gambling (1), poor adherence to oral naltrexone can be a problem (2).…”
Section: Monthly Injectable Naltrexone For Pathological Gamblingmentioning
confidence: 99%
“…Recently, we suggested the GLP-1 receptor agonist therapy as a potential treatment strategy for patients with schizophrenia and obesity 10. In a subsequent case report we provided the first clinical evidence in support of this idea 14.…”
Section: Introductionmentioning
confidence: 80%